The Use of Planting Media and Application of Leaf Fertilizer on the Growth and Yield of Mustard (Brassica Junea L.) in the Casino (Verticulture) Planting System - M Abror; Puji Hariyanto (Universitas Muhammadiyah Sidoarjo, 2016)
Nowadays land is being limited by development. Therefore, it is necessary to apply agri- cultural technology that can be utilized by land such as casino (verticulture) planting sys- tems. This study discusses the use of planting media and the application of leaf fertilizer on the growth and yield of mustard (Brassica juncea L.). The study was conducted in Pangkemiri Village, Tulangan District, Sidoarjo Regency from March to April 2015. This research involved factors using a group design (RBD) consisting of 2 factors, factor 1 using planting media consisting of water hyacinth (K1) ), bagasse (K2), banana stems (K3). Factor 2 is the use of a dose of leaf fertilizer consisting of: leaf fertilizer (L1), a dose of 1gr / liter of air (L2), a dose of 1.5 gr / liter of air (L3), a dose of 2gr / liter (L4). From these two factors, 12 combinations were obtained and repeated 3 times. The results showed that the use of water hyacinth growing media and the use of leaf fertilizer dosage 1.5gr / liter air (K1L2) gave the best results on the variable plant length, number of leaves, total weight, and selling weight.